2004
DOI: 10.1088/0953-8984/16/25/l01
|View full text |Cite
|
Sign up to set email alerts
|

Linear-scaling quantum Monte Carlo technique with non-orthogonal localized orbitals

Abstract: We have reformulated the quantum Monte Carlo (QMC) technique so that a large part of the calculation scales linearly with the number of atoms. The reformulation is related to a recent alternative proposal for achieving linear-scaling QMC, based on maximally localized Wannier orbitals (MLWO), but has the advantage of greater simplicity. The technique we propose draws on methods recently developed for linear-scaling density functional theory. We report tests of the new technique on the insulator MgO, and show th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…A local, grid-based non-orthogonal basis also used in linear scaling methods are blip functions (or b-splines) [41], which can be shown to be a form of finite element. They have also recently been used for linear scaling Quantum Monte Carlo calculations [56]. The psinc functions mentioned above, which are periodic bandwidth-limited delta functions, are another local basis set [52]; interestingly, almost the same functions were derived in the context of optimal local basis sets [57].…”
Section: Finite Elements and Local Real-space Basesmentioning
confidence: 99%
“…A local, grid-based non-orthogonal basis also used in linear scaling methods are blip functions (or b-splines) [41], which can be shown to be a form of finite element. They have also recently been used for linear scaling Quantum Monte Carlo calculations [56]. The psinc functions mentioned above, which are periodic bandwidth-limited delta functions, are another local basis set [52]; interestingly, almost the same functions were derived in the context of optimal local basis sets [57].…”
Section: Finite Elements and Local Real-space Basesmentioning
confidence: 99%
“…These results and approach can be expected to be used as reference for testing novel first-principles approaches for the evaluation of dielectrics properties. Although DMC calculations of susceptibilities are computational demanding, they can benefit, in terms of computational speed, from the use of order-N methods based on localized orthogonal [17,39] or nonorthogonal basis sets [40,41]. Therefore, it would be of great interest to determine the accuracy of the calculated dielectric properties when such approximations are used.…”
Section: Discussionmentioning
confidence: 99%
“…The number of such orbitals contributing at a point in space is independent of N which leads to the required improvement in scaling. Two different groups using the CASINO code have shown that this approach is extremely effective, namely Williamson, Hood, Grossman, and Reboredo [15,67], and Alfè and Gillan [68]. An impartial evaluation of the two different methods [69] showed that the latter was superior, and this was the approach finally adopted for the production version of CASINO.…”
Section: Improved Scaling Algorithmsmentioning
confidence: 99%